Utilizing Repetitive Sampling in the Construction of a Control Chart for Lindley Distribution with Time Truncation - G. V. Sriramachandran; Srinivasa Rao Gadde; Muhammad Aslam (Journal of Statistical Theory and Applications (JSTA))
Abstract The monitoring of the process relies on the average product lifetime, which adheres to the Lindley distribution and employs a truncated life test-based attribute control chart. Control limits for these charts are determined through a repetitive sampling procedure. Two inner and outer control limits are established based on the desired average run length (ARL). Tables are generated for varying ARL values by adjusting shift values while keeping the shape parameter of the Lindley distribution constant. The effectiveness of the control charts is assessed through application to real-time data, and the performance of the proposed chart is evaluated using simulation data. A comparative analysis is conducted with single sampling scheme based on ARL values, and the results are presented and discussed.